2018
DOI: 10.24293/ijcpml.v23i2.1134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Results of Analytical Profile Index and Disc Diffusion Antimicrobial Susceptibility Test to Technical Dedicated Reasonable 300b Method

Abstract: Angka kematian infeksi aliran darah cukup tinggi, berkisar 20–50%. Patogen penyebab dapat dibuktikan dengan pemeriksaan kulturdarah yang dilanjutkan dengan uji kepekaan antibiotika. Metode pemeriksaan dapat dilakukan secara manual atau automatis baiksemiautomatis ataupun automatis penuh. Metode manual relatif tidak memerlukan biaya yang besar dibandingkan metode automatisasi.Penelitian ini merupakan analisis observasional dengan desain potong lintang. Metode identifikasi manual memakai metode API danuji kepeka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The positive predictive value (PPV) and accuracy, however, were lower in TDR-300B than VITEK ® 2 ( Table 4). The Fisher' exact value for both comparison was >0.05, so there was no significant differences in the capability of and Gram-positive bacteria species [11]. In the present study, comparison of TDR-300B and VITEK ® 2 to VITEK ® -MS as gold standard showed that VITEK ® 2 has higher accuracy (92.31%) and PPV (92.00%) than TDR-300B (80.77% and 84.00%).…”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…The positive predictive value (PPV) and accuracy, however, were lower in TDR-300B than VITEK ® 2 ( Table 4). The Fisher' exact value for both comparison was >0.05, so there was no significant differences in the capability of and Gram-positive bacteria species [11]. In the present study, comparison of TDR-300B and VITEK ® 2 to VITEK ® -MS as gold standard showed that VITEK ® 2 has higher accuracy (92.31%) and PPV (92.00%) than TDR-300B (80.77% and 84.00%).…”
Section: Resultsmentioning
confidence: 40%
“…Many investigations have been conducted on VITEK ® 2 and, they showed the system was to give reliable results [6][7][8][9]. On the other hand, despite having similar system that is colorimetry based on the biochemical test array TDR-300B is relatively new and its performance has not been well reported [10]; one study thus far was reported by Sugiartha et al, 2017 [11]. In the developing country like Indonesia, this colorimetry-based identification system seems appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…After incubation the change in the color of all wells in noted. All the results are composed and a profile number is obtained which is then compared with profile numbers available online or in a commercial codebook for identification of bacterial species (Sugiartha et al 2018).…”
Section: Analytical Profile Index Testmentioning
confidence: 99%